Infecciones asociadas a drenaje ventricular al exterior: incidencia y factores de riesgo - Sáenz, Amparo; Argañaraz, Romina; Epelbaum, Carolina; Sanchez, Mariel; Mantese, Beatriz (Revista Argentina de Neurocirugía, 2020)
Introduction: The use of external ventricular drainage (EVD) is one of the most frequent procedures within neurosurgery. EVDs present a high infection rate, with values ​​ranging from 3-22%.Information about risk factors associated with EVD are limited to the northern hemisphere, therefore, the results are not so easily transferable to our environment. We believe that it is important to know the risk factors that predispose EVD´s infections in our community, in order to prevent and avoid them.Materials and methods: We performed a retrospective analytical study of a cohort of 66 pediatric patients who received 137 EVD. Risk factors for EVD infections were analyzed.Results: Of the 66 patients analyzed with EVD, 15 (22.7%; 95% CI: 14-34.5) presented an EVD infection. CSF fistula (65.2% vs 0%; p
Keywords: External Ventricular Drainage; Infections; Risk Factors; Pediatrics